A core-shell structure ternary positive electrode material for all-solid-state battery and a preparation method thereof and an all-solid-state battery
By adopting a ternary cathode material with a core-shell structure, combined with co-precipitation reaction and segmented calcination process, the high-nickel ternary cathode material has been solved, and the high cycle performance and rate performance of the all-solid-state battery is achieved.
Patent Information
- Application Number
- CN202211724055.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-30
AI Technical Summary
High-nickel ternary cathode material has problems of capacity attenuation and poor solid-solid interface contact in all solid-state lithium batteries, resulting in low cycling and rate performance of the battery.
A ternary cathode material using a core-shell structure has a core of LiNixCoyMn1-x-yO2 and a shell layer is LiNiaCobMn1-a-bO2 with a microporous structure. It is prepared by co-precipitation reaction and segmented calcination process, combined with in-situ coating of solid electrolytes, improving the interface compatibility between the material and the electrolyte.
The cycling performance and rate performance of all solid-state batteries is significantly improved, the cycling performance attenuation caused by volume changes in the battery is reduced, and the contact area between the positive electrode material and the solid electrolyte is improved, and the ion transmission efficiency is enhanced.
Smart Images

Figure BDA0004029013560000091 
Figure BDA0004029013560000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery materials, and specifically relates to a core-shell structure ternary positive electrode material for an all-solid-state battery, a preparation method thereof, and an all-solid-state battery. Background Art
[0002] All-solid-state lithium batteries (ASSLBs) have attracted extensive attention from scholars due to their good safety and wide working range, and are expected to gradually replace traditional lithium-ion batteries (LIBs) technology in the future. High-nickel ternary positive electrode materials have become the most likely common materials for all-solid-state lithium battery positive electrode materials due to their high energy density. They have problems such as continuous attenuation and poor thermal stability in all-solid-state lithium batteries. Moreover, the solid-solid interface between the electrode material of the all-solid-state lithium battery and the solid electrolyte has problems such as poor contact, high impedance, and low charging efficiency. At present, the positive electrode material is mainly improved by means of surface coating to improve its interfacial compatibility with the solid electrolyte. CN114759181A discloses a positive electrode material for solid-state batteries, a preparation method and an application thereof, wherein the preparation method is to uniformly coat the ternary precursor with PS microspheres in situ, and prepare a ternary positive electrode material with high porosity by calcining. CN112687882A discloses a high-specific-capacity high-nickel positive electrode material for solid-state batteries and a preparation method thereof. The preparation method comprises coating the surface of the high-nickel positive electrode material, and etching the coating layer with ammonia gas to form a microporous structure with a pore size of 5 to 10 nm.
[0003] In order to improve the capacity attenuation and poor solid-solid interface contact problems of high-nickel ternary positive electrode materials in all-solid-state batteries, the present invention develops a core-shell structure ternary positive electrode material for all-solid-state batteries to solve the above problems. Summary of the invention
[0004] The present invention provides a core-shell structure ternary positive electrode material for an all-solid-state battery, a preparation method thereof, and an all-solid-state battery to solve the above-mentioned technical problems.
[0005] One solution of the present invention is to provide a core-shell structure ternary positive electrode material for an all-solid-state battery, wherein the ternary positive electrode material is a core-shell structure, the particle size of the core-shell structure is 10 to 13 μm, the core-shell structure comprises a core and a shell layer, and the core is LiNi x Co y Mn 1-x-y O2 material, wherein 0.6≤x≤0.8, 0.1≤y≤0.3 and 1-xy>0, the particle size of the core is 3.0-5.0 μm, and the shell is LiNi with a microporous structure a Co b Mn 1-a-bO2 material, wherein 0.8≤a≤0.98, 0.01≤b≤0.1 and 1-ab>0, the micropores are formed by etching after sintering polyacrylonitrile particles embedded in the process of synthesizing the ternary precursor through a lithium calcination process.
[0006] Another solution of the present invention is to provide a method for preparing a core-shell structure ternary positive electrode material for an all-solid-state battery, comprising the steps of:
[0007] (1) Ni with core-shell structure x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The (OH)2 precursor and the lithium source are mixed and added into a mixer to prepare a mixture;
[0008] (2) calcining the mixture in stages under an oxygen atmosphere, and performing low-temperature heating, low-temperature insulation, high-temperature heating, high-temperature insulation, and cooling to obtain a ternary positive electrode material having a core-shell structure;
[0009] (3) In-situ coating of the ternary cathode material with a solid electrolyte to obtain a core-shell structure ternary cathode material for an all-solid-state battery.
[0010] As a preferred embodiment of the method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries according to the present invention, in step (1),
[0011] Ni x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The molar ratio of the metal element in the (OH)2 precursor to the lithium element in the lithium source is 1:1.04-1.10, the lithium source includes lithium hydroxide and / or lithium carbonate, the rotation speed of the mixer is 200-600r / min, and the mixing time is 2-5h.
[0012] As a preferred embodiment of the method for preparing a core-shell structured ternary positive electrode material for an all-solid-state battery according to the present invention, in step (1), the core-shell structured ternary positive electrode material
[0013] Ni x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The preparation method of (OH)2 precursor comprises the following steps:
[0014] (a) mixing a nickel source, a cobalt source and a manganese source to obtain a mixed metal salt solution A;
[0015] (b) mixing the mixed metal salt solution A, ammonia water and alkali solution, and performing a coprecipitation reaction under an inert atmosphere to obtain a core Ni x Co y Mn 1-x-y (OH)2 precursor;
[0016] (c) mixing a nickel source, a cobalt source, and a manganese source to obtain a mixed metal salt solution B, and mixing acrylonitrile, a polymerization inducing agent, and a solvent to obtain an acrylonitrile mixed solution;
[0017] (d) In the case of a core Ni x Co y Mn 1-x-y The mixed metal salt solution B, acrylonitrile mixed solution, ammonia water and alkaline solution are mixed in the bottom solution of (OH)2 precursor, and a coprecipitation reaction is performed again under an inert atmosphere to obtain Ni with a core-shell structure. x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b (OH)2 precursor.
[0018] As a preferred embodiment of the method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries described in the present invention, in step (a), the molar concentration of the nickel element in the mixed metal salt solution A is 0.3-1.6 mol / L, the molar concentration of the cobalt element is 0.1-0.8 mol / L, the molar concentration of the manganese element is 0.01-0.1 mol / L, and the total molar concentration of the metal elements is 0.5-2.0 mol / L.
[0019] As a preferred embodiment of the method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries described in the present invention, in step (b), the pH of the coprecipitation reaction is 10.0-12.0, and the concentration of the ammonia water is 0.05-0.30 mol / L; in step (d), the pH of the coprecipitation reaction is 9.5-11.0, and the concentration of the ammonia water is 0.10-1.00 mol / L.
[0020] As a preferred embodiment of the method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries according to the present invention, in step (c), the molar concentration of the nickel element in the mixed metal salt solution B is 0.4-1.96 mol / L, the molar concentration of the cobalt element is 0.01-0.4 mol / L, the molar concentration of the manganese element is 0.01-0.09 mol / L, the total molar concentration of the metal elements is 0.5-2.0 mol / L, the concentration of acrylonitrile in the acrylonitrile mixed solution is 2-50 g / L, and the concentration of the polymerization inducer is 0.5-5 g / L.
[0021] As a preferred embodiment of the method for preparing the core-shell structure ternary positive electrode material for an all-solid-state battery according to the present invention, the nickel source includes any one or more of nickel chloride, nickel nitrate, nickel sulfate, and nickel acetate; the cobalt source includes any one or more of cobalt chloride, cobalt nitrate, cobalt sulfate, and cobalt acetate; the manganese source includes any one or more of manganese chloride, manganese nitrate, manganese sulfate, and manganese acetate; the alkali solution includes any one of sodium carbonate solution, sodium bicarbonate solution, and sodium hydroxide; the gas of the inert atmosphere includes any one of high-purity nitrogen and high-purity argon, or a mixture of the two; and the polymerization inducer includes azobisisobutyronitrile.
[0022] As a preferred embodiment of the method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries described in the present invention, in step (2), the temperature of the low-temperature heating is 250-500°C, the time of the low-temperature insulation is 1-4 hours, the temperature of the high-temperature heating is 700-950°C, the time of the high-temperature insulation is 6-12 hours, and the cooling refers to natural cooling to room temperature.
[0023] The third solution of the present invention is to provide an all-solid-state battery, comprising: a positive electrode plate, wherein the positive electrode plate contains a core-shell structure ternary positive electrode material for an all-solid-state battery, and the core-shell structure ternary positive electrode material for an all-solid-state battery is prepared by the preparation method of the core-shell structure ternary positive electrode material for an all-solid-state battery.
[0024] The core-shell structure ternary positive electrode material for an all-solid-state battery and its preparation method and all-solid-state battery proposed in the present invention have the following advantages compared with the prior art:
[0025] 1. The present invention introduces polyacrylonitrile particles by in-situ doping when preparing the shell material, and uniformly forms pores in the shell through a subsequent calcination process, which helps to achieve good contact between the solid-solid interface of the positive electrode material and the solid electrolyte, reduce the interface resistance, and improve the cycle performance and rate performance of the battery;
[0026] 2. The core-shell structured ternary positive electrode material for the all-solid-state battery provided by the present invention has almost no volume change during the battery charging and discharging process, so that the overall volume and structure of the all-solid-state battery will not produce obvious deformation, effectively suppressing the cycle performance attenuation of the all-solid-state battery caused by volume change. DETAILED DESCRIPTION
[0027] The present invention provides a ternary positive electrode material with a core-shell structure, wherein the core is LiNi x Co y Mn 1-x-y O2 material, wherein 0.6≤x≤0.8, 0.1≤y≤0.3, and 1-xy>0, the core particle size is 3.0~5.0μm, and the shell layer is LiNi with microporous structure a Co b Mn 1-a-b O2 material, wherein 0.8≤a≤0.98, 0.01≤b≤0.1, and 1-ab>0, the particle size of the core-shell structure ternary positive electrode material is 10-13 μm, and the preparation method thereof comprises the following steps:
[0028] 1. Ni with core-shell structure x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The (OH)2 precursor and the lithium source are mixed and added into a mixer, the mixer speed is 200-600 r / min, and the mixing time is 2-5 h to obtain a mixture;
[0029] The above Ni x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The molar ratio of the metal element in the (OH)2 precursor to the lithium element in the lithium source is 1:(1.04-1.10); the lithium source includes lithium hydroxide and / or lithium carbonate;
[0030] The above-mentioned Ni with core-shell structure x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b (OH)2 precursor, comprising the following steps:
[0031] (a) mixing a nickel source, a cobalt source and a manganese source to obtain a mixed metal salt solution A;
[0032] (b) Mixing the mixed metal salt solution A, ammonia water and alkali solution, and performing a coprecipitation reaction under an inert atmosphere to obtain a core Ni x Co y Mn 1-x-y (OH)2 precursor;
[0033] (c) mixing a nickel source, a cobalt source, and a manganese source to obtain a mixed metal salt solution B, and mixing acrylonitrile, a polymerization inducing agent, and a solvent to obtain an acrylonitrile mixed solution;
[0034] (d) In the case of a core Ni x Co y Mn 1-x-y In the bottom solution of (OH)2 precursor, mixed metal salt solution B, acrylonitrile mixed solution, ammonia water and alkali solution are mixed and co-precipitated again under an inert atmosphere to obtain Ni with core-shell structure. x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b (OH)2 precursor.
[0035] The nickel source comprises one or more of nickel chloride, nickel nitrate, nickel sulfate and nickel acetate; the cobalt source comprises one or more of cobalt chloride, cobalt nitrate, cobalt sulfate and cobalt acetate; the manganese source comprises one or more of manganese chloride, manganese nitrate, manganese sulfate and manganese acetate; the alkali solution comprises one of sodium carbonate solution, sodium bicarbonate solution and sodium hydroxide; the gas of the inert atmosphere comprises one of high-purity nitrogen and high-purity argon or a mixture of the two; the polymerization inducer comprises azobisisobutyronitrile; the molar concentration of nickel element in the mixed metal salt solution A is 0.3-1.6 mol / L, the molar concentration of cobalt element is 0.1-0.8 mol / L, the molar concentration of manganese element is 0.01-0.1 mol / L, and the total molar concentration of metal elements is 0.5-2.0 mol / L; the mixed metal salt solution A, ammonia water and alkali solution are added to the mixture. The reaction conditions of the liquid are as follows: pH 10.0-12.0, ammonia concentration 0.05-0.30 mol / L; the molar concentration of nickel element in the mixed metal salt solution B is 0.4-1.96 mol / L, the molar concentration of cobalt element is 0.01-0.4 mol / L, the molar concentration of manganese element is 0.01-0.09 mol / L, and the total molar concentration of metal elements is 0.5-2.0 mol / L; the reaction conditions of the mixed metal salt solution B, acrylonitrile mixed solution, ammonia water and alkali solution are as follows: pH 9.5-11.0, ammonia concentration 0.10-1.00 mol / L; the concentration of acrylonitrile in the acrylonitrile mixed solution is 2-50 g / L, and the concentration of the polymerization inducer is 0.5-5 g / L; the solvent is any one of dimethylformamide and dimethylacetamide.
[0036] 2. The mixture is calcined in stages under an oxygen atmosphere, and subjected to low-temperature heating, low-temperature insulation, continued high-temperature heating, high-temperature insulation, and cooling to obtain a core-shell structured ternary positive electrode material;
[0037] The temperature of the low temperature heating is 250-500°C, the low temperature insulation time is 1-4 hours, the temperature of the high temperature heating is 700-950°C, the high temperature insulation time is 6-12 hours, and it is naturally cooled to room temperature;
[0038] 3. The core-shell structure ternary positive electrode material is in-situ coated with a solid electrolyte to obtain a core-shell structure ternary positive electrode material for an all-solid-state battery.
[0039] The ternary positive electrode material prepared by the above method can be used to prepare positive electrode plates, and the prepared positive electrode plates can be used to prepare all-solid-state batteries.
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.
[0041] First, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0042] For specific implementation and related comparison, please refer to the following embodiments:
[0043] Example 1
[0044] The method for preparing a novel core-shell structure ternary positive electrode material for an all-solid-state battery according to the present invention comprises the following steps:
[0045] (1) Weigh a certain amount of nickel sulfate, cobalt sulfate, and manganese sulfate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 8:1:1 to prepare a mixed solution A with a metal concentration of 1.6 mol / L, slowly add ammonia water and sodium hydroxide solution, adjust the pH to 11.5, and the ammonia concentration to 0.05 mol / L, maintain this reaction condition and react under the protection of high-purity nitrogen until the particle size is 3.5 μm, and obtain a core Ni8Co1Mn1(OH)2 precursor;
[0046] (2) Weigh a certain amount of nickel sulfate, cobalt sulfate, and manganese sulfate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 98:1:1 to prepare a mixed solution B with a metal concentration of 1.5 mol / L, add 20 g of acrylonitrile monomer and 10 g of azobisisobutyronitrile into the solvent to prepare an acrylonitrile mixed solution, add the Ni8Co1Mn1(OH)2 precursor prepared in step (1) into the mixed solution B, slowly add ammonia water, sodium hydroxide solution, and acrylonitrile mixed solution, adjust the pH to 10.2, and the ammonia concentration to 0.36 mol / L, maintain this reaction condition and react under the protection of high-purity nitrogen until the particle size is 13.0 μm, and obtain
[0047] Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor;
[0048] (3) Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor and lithium hydroxide were mixed in a molar ratio of metal element to lithium element of 1:1.06 and added into a mixer at a rotation speed of 400r / min for 3 hours. The mixture was kept at 350°C for 4 hours and then at 800°C for 8 hours in an oxygen atmosphere. After naturally cooling to room temperature, the material was in-situ coated with a solid electrolyte to obtain a core-shell structured ternary positive electrode material for all-solid-state batteries.
[0049] Example 2
[0050] The method for preparing a novel core-shell structure ternary positive electrode material for an all-solid-state battery according to the present invention comprises the following steps:
[0051] (1) Weigh a certain amount of nickel chloride, cobalt chloride, and manganese chloride, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 7:1:2 to prepare a mixed solution A with a metal concentration of 0.5 mol / L, slowly add ammonia water and sodium carbonate solution, adjust the pH to 12.0, and the ammonia concentration to 0.16 mol / L, maintain this reaction condition and react under the protection of high-purity nitrogen until the particle size is 3.0 μm, and obtain a core Ni8Co1Mn1(OH)2 precursor;
[0052] (2) Weigh a certain amount of nickel chloride, cobalt chloride, and manganese chloride, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 95:3:2 to obtain a mixed solution B with a metal concentration of 1.8 mol / L, add 30 g of acrylonitrile monomer and 15 g of azobisisobutyronitrile into the solvent to mix into an acrylonitrile mixed solution, add the Ni8Co1Mn1(OH)2 precursor obtained in step (1) into the mixed solution B, slowly add ammonia water, sodium carbonate solution, and acrylonitrile mixed solution, adjust the pH to 11.0, and the ammonia concentration to 1.00 mol / L, maintain this reaction condition, and react under the protection of high-purity nitrogen until the particle size is 12.5 μm, to obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor;
[0053] (3) Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor and lithium hydroxide were mixed in a molar ratio of metal element to lithium element of 1:1.04 and added into a mixer at a rotation speed of 200r / min and mixed for 5 hours. The mixture was first kept at 300°C for 3 hours and then at 700°C for 12 hours in an oxygen atmosphere. After naturally cooling to room temperature, the material was in-situ coated with a solid electrolyte to obtain a core-shell structured ternary positive electrode material for all-solid-state batteries.
[0054] Example 3
[0055] The method for preparing a novel core-shell structure ternary positive electrode material for an all-solid-state battery according to the present invention comprises the following steps:
[0056] (1) Weigh a certain amount of nickel acetate, cobalt acetate, and manganese acetate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 6:2:2 to prepare a mixed solution A with a metal concentration of 0.3 mol / L, slowly add ammonia water and sodium bicarbonate solution, adjust the pH to 10.0, and the ammonia concentration to 0.30 mol / L, maintain this reaction condition and react under the protection of high-purity argon until the particle size is 5.0 μm, and obtain a core Ni8Co1Mn1(OH)2 precursor;
[0057] (2) Weigh a certain amount of nickel acetate, cobalt acetate, and manganese acetate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 8:1:1 to obtain a mixed solution B with a metal concentration of 0.5 mol / L, add 10 g of acrylonitrile monomer and 5 g of azobisisobutyronitrile into the solvent to mix into an acrylonitrile mixed solution, add the Ni8Co1Mn1(OH)2 precursor obtained in step (1) into the mixed solution B, slowly add ammonia water, sodium bicarbonate solution, and acrylonitrile mixed solution, adjust the pH to 9.5, and the ammonia concentration to 0.83 mol / L, maintain this reaction condition and react under the protection of high-purity argon until the particle size is 10.0 μm, and obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor;
[0058] (3) Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor and lithium hydroxide were mixed in a molar ratio of metal element to lithium element of 1:1.08 and added into a mixer at a speed of 600r / min and mixed for 2h. The mixture was first kept at 250°C for 4h and then at 950°C for 6h in an oxygen atmosphere. After naturally cooling to room temperature, the material was in-situ coated with a solid electrolyte to obtain a core-shell structured ternary positive electrode material for all-solid-state batteries.
[0059] Example 4
[0060] (1) Weigh a certain amount of nickel nitrate, cobalt nitrate, and manganese nitrate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 6:3:1 to prepare a mixed solution A with a metal concentration of 0.8 mol / L, slowly add ammonia water and sodium hydroxide solution, adjust the pH to 10.8, and the ammonia concentration to 0.22 mol / L, maintain this reaction condition and react under the protection of high-purity argon until the particle size is 4.5 μm, and obtain a core Ni8Co1Mn1(OH)2 precursor;
[0061] (2) Weigh a certain amount of nickel nitrate, cobalt nitrate, and manganese nitrate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 96:2:2 to obtain a mixed solution B with a metal concentration of 2.0 mol / L, add 20 g of acrylonitrile monomer and 10 g of azobisisobutyronitrile into the solvent to obtain an acrylonitrile mixed solution, add the Ni8Co1Mn1(OH)2 precursor obtained in step (1) into the mixed solution B, slowly add ammonia water, sodium hydroxide solution, and acrylonitrile mixed solution, adjust the pH to 10.9, and the ammonia concentration to 0.10 mol / L, maintain this reaction condition, and react under the protection of high-purity argon until the particle size is 12.0 μm, to obtain
[0062] Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor;
[0063] (3) Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor and lithium hydroxide were mixed in a molar ratio of metal element to lithium element of 1:1.10 and added into a mixer at a rotation speed of 500r / min and mixed for 3.5h. The mixture was first kept at 500℃ for 1h and then at 900℃ for 7h in an oxygen atmosphere. After naturally cooling to room temperature, the material was in-situ coated with a solid electrolyte to obtain a core-shell structured ternary positive electrode material for all-solid-state batteries.
[0064] Comparative Example 1
[0065] (1) Weigh a certain amount of nickel sulfate, cobalt sulfate, and manganese sulfate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 8:1:1 to prepare a mixed solution A with a metal concentration of 1.6 mol / L, slowly add ammonia water and sodium hydroxide solution, adjust the pH to 11.5, and the ammonia concentration to 0.05 mol / L, maintain this reaction condition and react under the protection of high-purity nitrogen until the particle size is 3.5 μm, and obtain a core Ni8Co1Mn1(OH)2 precursor;
[0066] (2) Weigh a certain amount of nickel sulfate, cobalt sulfate, and manganese sulfate, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 98:1:1 to obtain a mixed solution B with a metal concentration of 1.5 mol / L, add the Ni8Co1Mn1(OH)2 precursor obtained in step (1) to the mixed solution B, slowly add ammonia water and sodium hydroxide solution, adjust the pH to 10.2, and the ammonia concentration to 0.36 mol / L, maintain this reaction condition and react under the protection of high-purity nitrogen until the particle size is 13.0 μm, and obtain Ni0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor;
[0067] (3) Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 The (OH)2 precursor and lithium hydroxide were mixed in a molar ratio of metal element to lithium element of 1:1.06 and added into a mixer at a rotation speed of 400r / min for 3 hours. The mixture was kept at 350°C for 4 hours and then at 800°C for 8 hours in an oxygen atmosphere. After naturally cooling to room temperature, the material was in-situ coated with a solid electrolyte to obtain a core-shell structured ternary positive electrode material for all-solid-state batteries.
[0068] Comparative Example 2
[0069] (1) Weigh a certain amount of nickel chloride, cobalt chloride, and manganese chloride, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 7:1:2 to prepare a mixed solution A with a metal concentration of 0.5 mol / L, slowly add ammonia water and sodium carbonate solution, adjust the pH to 12.0, and the ammonia concentration to 0.16 mol / L, maintain this reaction condition and react under the protection of high-purity nitrogen until the particle size is 3.0 μm, and obtain a core Ni8Co1Mn1(OH)2 precursor;
[0070] (2) Weigh a certain amount of nickel chloride, cobalt chloride, and manganese chloride, add water and mix according to the molar ratio of nickel, cobalt, and manganese of 95:3:2 to obtain a mixed solution B with a metal concentration of 1.8 mol / L, add the Ni8Co1Mn1(OH)2 precursor obtained in step (1) to the mixed solution B, slowly add ammonia water and sodium carbonate solution, adjust the pH to 11.0, and the ammonia concentration to 1.00 mol / L, maintain this reaction condition and react under the protection of high-purity nitrogen until the particle size is 12.5 μm, and obtain Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01 (OH)2 precursor;
[0071] (3) Ni 0.8 Co 0.1 Mn 0.1 (OH)2—Ni 0.98 Co 0.01 Mn 0.01The (OH)2 precursor and lithium hydroxide were mixed in a molar ratio of metal element to lithium element of 1:1.04 and added into a mixer at a rotation speed of 200r / min and mixed for 5 hours. The mixture was first kept at 300°C for 3 hours and then at 700°C for 12 hours in an oxygen atmosphere. After naturally cooling to room temperature, the material was in-situ coated with a solid electrolyte to obtain a core-shell structured ternary positive electrode material for all-solid-state batteries.
[0072] A mixture of the above-mentioned embodiments or comparative samples and Li10GeP2S12 was used as the positive electrode, Li10GeP2S12 was used as the electrolyte, and Li-In was used as the negative electrode to assemble an all-solid-state battery, and constant current charge and discharge were performed at room temperature with a voltage range of 2.9 to 3.7 V and a current density of 100 mA / g (0.5C rate) for 100 charge and discharge cycles; the lithium ion diffusion coefficients of different materials were tested using an electrochemical impedance spectroscopy test.
[0073] The test results of the comparative examples and embodiments are shown in Table 1 below:
[0074]
[0075]
[0076] Table 1
[0077] It can be seen from Table 1 that the all-solid-state batteries assembled from the core-shell structured ternary positive electrode materials obtained in Examples 1-4 of the present invention show excellent charge and discharge performance and cycle performance after electrochemical testing; Comparative Examples 1-2 do not perform in-situ doping with polyacrylonitrile, and have a lower lithium ion diffusion coefficient than the embodiments, which indicates that the core-shell structured ternary positive electrode material with a porous shell in the embodiments can have a faster transmission rate in the solid electrolyte, thereby obtaining a higher charge and discharge capacity.
[0078] In summary, the present invention prepares a ternary precursor of a core-shell structure through a coprecipitation reaction and in-situ dopes polyacrylonitrile particles in the shell layer, with the purpose of utilizing the core-shell structure to inhibit the volume change caused by the electrode material during the charge and discharge process, thereby reducing the cycle performance of the battery, and at the same time utilizing the in-situ doping method to uniformly form pores in the shell structure, increase the contact area between the positive electrode material and the solid electrolyte, establish a more efficient ion transmission efficiency, and improve the cycle performance and rate performance of the battery.
[0079] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a core-shell structure ternary positive electrode material for an all-solid-state battery, characterized in that: Includes steps: (1) Ni with core-shell structure x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The (OH)2 precursor and the lithium source are mixed and added into a mixer to obtain a mixture. Wherein, the Ni having a core-shell structure x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The preparation method of (OH)2 precursor comprises the following steps: (a) mixing a nickel source, a cobalt source and a manganese source to obtain a mixed metal salt solution A; (b) mixing the mixed metal salt solution A, ammonia water and alkali solution, and performing a coprecipitation reaction under an inert atmosphere to obtain a core Ni x Co y Mn 1-x-y (OH)2 precursor; (c) mixing a nickel source, a cobalt source, and a manganese source to obtain a mixed metal salt solution B, and mixing acrylonitrile, a polymerization inducer, and a solvent to obtain an acrylonitrile mixed solution; (d) In the case of a core Ni x Co y Mn 1-x-y The mixed metal salt solution B, acrylonitrile mixed solution, ammonia water and alkaline solution are mixed in the bottom solution of (OH)2 precursor, and a coprecipitation reaction is performed again under an inert atmosphere to obtain Ni with a core-shell structure. x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b (OH)2 precursor; (2) calcining the mixture in stages under an oxygen atmosphere, and obtaining a ternary positive electrode material having a core-shell structure through low-temperature heating, low-temperature insulation, high-temperature heating, high-temperature insulation, and cooling, wherein the low-temperature heating temperature is 250 to 500° C., the low-temperature insulation time is 1 to 4 hours, the high-temperature heating temperature is 700 to 950° C., the high-temperature insulation time is 6 to 12 hours, and the cooling refers to natural cooling to room temperature; (3) In-situ coating of the ternary cathode material with a solid electrolyte to obtain a core-shell structure ternary cathode material for an all-solid-state battery, wherein the ternary cathode material is a core-shell structure, the particle size of the core-shell structure is 10 to 13 μm, the core-shell structure comprises a core and a shell, and the core is LiNi x Co y Mn 1-x-y O2 material, wherein 0.6≤x≤0.8, 0.1≤y≤0.3 and 1-xy>0, the particle size of the core is 3.0-5.0 μm, and the shell is LiNi with a microporous structure a Co b Mn 1-a-b O2 material, wherein 0.8≤a≤0.98, 0.01≤b≤0.1 and 1-ab>0, the micropores are formed by etching after sintering polyacrylonitrile particles embedded in the synthesis of the ternary precursor through a lithium calcination process.
2. The method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries according to claim 1, characterized in that: In step (1), the Ni x Co y Mn 1-x-y (OH)2—Ni a Co b Mn 1-a-b The molar ratio of the metal element in the (OH)2 precursor to the lithium element in the lithium source is 1:1.04-1.10, the lithium source includes lithium hydroxide and / or lithium carbonate, the rotation speed of the mixer is 200-600r / min, and the mixing time is 2-5h.
3. The method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries according to claim 1, characterized in that: In step (a), the molar concentration of nickel element in the mixed metal salt solution A is 0.3-1.6 mol / L, the molar concentration of cobalt element is 0.1-0.8 mol / L, the molar concentration of manganese element is 0.01-0.1 mol / L, and the total molar concentration of metal elements is 0.5-2.0 mol / L.
4. The method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries according to claim 1, characterized in that: In step (b), the pH of the coprecipitation reaction is 10.0-12.0, and the concentration of the aqueous ammonia is 0.05-0.30 mol / L; in step (d), the pH of the coprecipitation reaction is 9.5-11.0, and the concentration of the aqueous ammonia is 0.10-1.00 mol / L.
5. The method for preparing the core-shell structure ternary positive electrode material for all-solid-state batteries according to claim 1, characterized in that: In step (c), the molar concentration of nickel element in the mixed metal salt solution B is 0.4-1.96 mol / L, the molar concentration of cobalt element is 0.01-0.4 mol / L, the molar concentration of manganese element is 0.01-0.09 mol / L, the total molar concentration of metal elements is 0.5-2.0 mol / L, the concentration of acrylonitrile in the acrylonitrile mixed solution is 2-50 g / L, and the concentration of the polymerization inducer is 0.5-5 g / L.
6. The method for preparing the core-shell structure ternary cathode material for all-solid-state batteries according to claim 1, characterized in that: The nickel source includes any one or more of nickel chloride, nickel nitrate, nickel sulfate, and nickel acetate; the cobalt source includes any one or more of cobalt chloride, cobalt nitrate, cobalt sulfate, and cobalt acetate; the manganese source includes any one or more of manganese chloride, manganese nitrate, manganese sulfate, and manganese acetate; the alkali solution includes any one of sodium carbonate solution, sodium bicarbonate solution, and sodium hydroxide; the gas of the inert atmosphere includes any one of high-purity nitrogen and high-purity argon, or a mixed gas of the two; and the polymerization inducer includes azobisisobutyronitrile.
7. An all-solid-state battery, characterized in that: include: A positive electrode plate, wherein the positive electrode plate comprises a core-shell structure ternary positive electrode material for an all-solid-state battery, wherein the core-shell structure ternary positive electrode material for an all-solid-state battery is prepared by the method for preparing the core-shell structure ternary positive electrode material for an all-solid-state battery according to any one of claims 1 to 6.
Citation Information
Patent Citations
Special high-specific-capacity high-nickel positive electrode material for solid-state battery and preparation method thereof
CN112687882A
Positive electrode material for solid-state battery as well as preparation method and application of positive electrode material
CN114759181A
Positive electrode material for power batteries
CN108054375A
Long-circulation and low-expansion silicon-carbon composite material with inner hole structure as well as preparation method and application of long-circulation and low-expansion silicon-carbon composite material
CN114142005A